Suitable grazing during the regrowth period promotes plant diversity in winter pastures in the Qinghai-Tibetan plateau - Wei, Wanrong; Zhang, Yan; Tang, Zhongmin; An, Shenghui; Zhen, Qiaoyan; Qin, Mingsen; He, Jundong; Oosthuizen, Maria K. (Frontiers in Ecology and Evolution, 2022)
Vegetation is a crucial component of any ecosystem and to preserve the health and stability of grassland ecosystems, species diversity is important. The primary form of grassland use globally is livestock grazing, hence many studies focus on how plant diversity is affected by the grazing intensity, differential use of grazing time and livestock species. Nevertheless, the impact of the grazing time on plant diversity remains largely unexplored. We performed a field survey on the winter pastures in alpine meadows of the Qinghai-Tibetan Plateau (QTP) to examine the effects of grazing time on the vegetation traits. Livestock species, grazing stocking rates and the initiation time of the grazing were similar, but termination times of the grazing differed. The grazing termination time has a significant effect on most of the vegetation traits in the winter pastures. The vegetation height, above-ground biomass, and the Graminoids biomass was negatively related to the grazing termination time in the winter pastures. In contrast, vegetation cover and plant diversity initially increased and subsequently decreased again as the grazing termination time was extended. An extension of the grazing time did not have any effect on the biomass of forbs. Our study is the first to investigate the effects of grazing during the regrowth period on vegetation traits and imply that the plant diversity is mediated by the grazing termination time during the regrowth period in winter pastures. These findings could be used to improve the guidelines for livestock grazing management and policies of summer and winter pasture grazing of family pastures on the QTP from the perspective of plant diversity protection.